Analisis Tegangan Keluaran Generator Listrik Frekuensi Rendah dengan Metode Conjugate-Gradient - Jamrud Aminuddin (Jurnal Teras Fisika: Teori, Modeling, dan Aplikasi Fisika, 2020)
The numerical analysis of the output voltage of the electric generators based on the electromagnetic induction equation has been carried out using the conjugate-gradient method. The physical parameters used as constant numbers are from the experimental results of the electric generator with lower frequency, i.e.: the permanent magnet, cross-sectional area, and the angle between the magnetic field and the magnetic moment. The others parameter considered in the conjugate gradient-method are the number of coils of the solenoid and the output voltage which is generated from the kinetic energy. The results of the calculation show that the error rate of the method is approximately 5%. Overall, this numerical analysis shows that the output voltage can be balanced through the adjustment of the number of coils of the solenoid and the rotational speed of the generator.